A Mathematical Model and algorithm for Optimal Acceptance Control of the Reliability of Hierarchical Space Technology Systems in Conditions of Single and Small-Scale Production - Marat Sh. Nasibulin; Valery B. Rudakov (RUDN Journal of Engineering Research)
The problem of statistical acceptance control of reliability of complex space technology systems in a two-level hierarchical structure is considered: in the production of space technology products that make up the hierarchical system of space technology, and in the production of the system as a whole. A mathematical model and algorithm for determining optimal reliability control plans in this structure have been developed. Control plans are interrelated and optimal in terms of minimizing the target functions of the economic costs of control and losses associated with the risks of making erroneous decisions, which are truncated. The model and algorithm make it possible to take into account the results of reliability control of the products that make up the system when planning optimal reliability control of the system as a whole, which will reduce the economic costs of control and losses when confirming the high requirements for reliability of complex space technology systems in conditions of lack of statistical information.